PENGARUH RISIKO BISNIS, UKURAN PERUSAHAAN, KURS DAN SUKU BUNGA TERHADAP FINANCIAL DISTRESS (STUDI PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021) - Azhari Nisa; Haryetti Haryetti; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the effect of business risk, firm size, exchange rate andinterest rates on financial distress. The population in this study includes alltransportation companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021 as many as 52 companies. The sampling technique used was purposivesampling method with the number of samples that met the criteria of 40companies. The results showed that business risk and exchange rate had asignificant positive effect on financial distress. Firm size has a significantnegative effect on financial distress and interest rate have no significant positiveeffect on financial distress. Keywords: Business Risk, Company Size, Exchange Rate, Interest Rate, FinancialDistress